Virtual Reality dan Kultur In-Vitro Sebagai Media Edukasi Meningkatkan Minat Generasi Z Pada Pertanian - Wirya, Gusti Ngurah Alit Susanta; Dewi, Ni Luh Made Indah Murdyani; Utari, Ni Kadek Sri; Arisena, Gede Mekse Korri; Fitriani, Yuyun; Dharmadiatmika, I Made Agus; Wibisana, I Made Dicky Chandra; Devi, Ni Luh Putu Hartika Sinta; Wulandari, Ni Kadek Pingkan (Universitas Prof. Dr. Moestopo (Beragama), 2026)
This community service program was carried out at Kerambitan 1 Public High School based on the low interest of Generation Z in agriculture due to their limited understanding of the use of modern technology in this sector. This activity aimed to increase students' interest and understanding of agriculture through counseling and workshops with three main topics, namely in vitro culture technology, the use of digital technology in landscape architecture, and agribusiness concepts, which were then complemented by tree planting in the school environment. The results of the activity showed a significant increase in both the students' knowledge and interest. More than 80% of students understood the material after the activity, with the largest increase in the topic of in vitro culture (from 30.0% to 85.7%). Students' interest in continuing their studies in agriculture also increased from 32.9% to 68.6%. In addition, the tree planting activity with teachers, lecturers, and KKN students fostered environmental awareness and the importance of sustainability. The conclusion of this activity is that the integration of theoretical learning, technological practice, and real environmental action can increase students' enthusiasm in understanding modern agriculture, with the added benefit of a collaborative and interactive approach.